2020
DOI: 10.1096/fj.202000827rr
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA TUG1 competitively binds to miR‐340 to accelerate myocardial ischemia‐reperfusion injury

Abstract: The aberrant expression of long noncoding RNA (lncRNA) taurine-upregulated gene 1 (TUG1) has been previously associated with myocardial ischemia-reperfusion injury (MIRI), but the underlying molecular mechanisms remain elusive. The current study aimed to clarify the functional role of TUG1/microRNA (miR)-340/histone deacetylase 4 (HDAC4)/β-catenin/glucose transporter type 1 (GLUT1) axes in MIRI. The database-based analyses performed predicted the downstream factors of lncRNA TUG1. In the MIRI mouse models and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…Accumulating evidence suggests that miR-340-5p increases the expression levels of Bim, Bax, and cleaved caspase 3 but decreases the expression of Bcl-2, thereby contributing to increased apoptosis [ 12 , 13 , 30 ]. However, another study has reported that microRNA-340-5p plays a protective role in hypoxia/reoxygenation-induced apoptosis in an acute myocardial infarction model [ 46 ]. The difference in the response period for the animal model should be considered because the development of cardiomyopathy is chronic and progressive.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that miR-340-5p increases the expression levels of Bim, Bax, and cleaved caspase 3 but decreases the expression of Bcl-2, thereby contributing to increased apoptosis [ 12 , 13 , 30 ]. However, another study has reported that microRNA-340-5p plays a protective role in hypoxia/reoxygenation-induced apoptosis in an acute myocardial infarction model [ 46 ]. The difference in the response period for the animal model should be considered because the development of cardiomyopathy is chronic and progressive.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lou Z et al found that there are 1395 LncRNA differential expressions in human ischemia-reperfusion myocardial tissue through LncRNA microarray analysis [ 7 ]. A recent research reported that LncRNA TUG1 competitively binds to miR-340, thereby accelerating MIRI [ 8 ]. Additionally, studies have revealed that lncRNA ROR/miR-124-3p/TRAF6 axis regulation acts pivotally in MIRI-induced inflammatory response in human cardiomyocytes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…GLUT1 inhibits mitochondrial dysfunction and diminishes structural remodeling during pressure overload. Besides, the in vivo experiments in mice validated that the suppression of TUG1/miR‐340/HDAC4/β‐catenin/GLUT1 axes directed the reduction of MIRI 38 …”
Section: Apoptosismentioning
confidence: 81%
“…Silencing of TUG1 led to inhibition of cervical cancer cell proliferation mediated by miR‐381‐3/MDM2 107 . TUG1 elevation is also relevant in myocardial ischemia–reperfusion injury (MIRI) 38 . TUG1 binds to miR340, and then it acts like a sponge.…”
Section: Apoptosismentioning
confidence: 99%